KINERJA KOMISI PENYIARAN INDONESIA DAERAH PROVINSI KEPULAUAN RIAU - Mukhamad Rofik; Faizal Madya (Jurnal Paradigma (JP), 2021)
The purpose of this study is to describe and analyze the performance of the Regional Indonesian Broadcasting Commission (KPID) of the Riau Islands Province (Kepulauan Riau) using a balanced scorecard, with a qualitative method. Collecting data by in-depth interviews, literature study, documentation study, observation. Test the validity of the data by triangulation. The research focus includes performance analysis from a financial perspective, a customer perspective, an internal business process perspective and a learning and growth perspective. From the research results it can be concluded that the performance of KPID as a whole shows poor results. Factors that influence the poor performance of KPID, especially the financial aspect, are the lack of budget support for the provincial government budget grants in the Riau Islands.Keywords: Performance, Regional Indonesian Broadcasting Commission, Balanced Scorecard